1990
DOI: 10.1172/jci114791
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase and butyrylcholinesterase genes coamplify in primary ovarian carcinomas.

Abstract: The genes for acetylcholinesterase (ACHE) and butyrylcholinesterase (CHE) are expressed in multiple tumor tissues, including ovarian carcinomas. Both CHE and ACHE genes coamplify in leukemias. To examine the relationship of gene amplification to the expression of these genes in tumors, ACHE and CHE genes and their expression were studied in primary ovarian carcinomas. DNA blot hybridization demonstrated a significant amplification and mutagenesis of both genes in 6 of 11 malignant tumors studied. This was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Its sequence further predicts responses to cAMP-inducing stimuli and signal transduction pathways in nervous system cell lineages as well as control by additional distant enhancer sequences, in good agreement with the multiplicity of human tissues and developmental stages where the AcChoEase protein has been observed (6). Furthermore, binding sites for early/immediate gene products (i.e., E-Box and Egrl) may explain AcChoEase expression in tumor tissues and may relate to the tumorigenic amplification of this gene (27,28). The existence of an NF-KB element within the first intron could possibly imply that expression of the ACHE gene in lymphocytes is subject to regulation by transcription factors binding this intron and affecting cell cycle-related control, limited to the Go-G1 transition phase (16).…”
supporting
confidence: 66%
“…Its sequence further predicts responses to cAMP-inducing stimuli and signal transduction pathways in nervous system cell lineages as well as control by additional distant enhancer sequences, in good agreement with the multiplicity of human tissues and developmental stages where the AcChoEase protein has been observed (6). Furthermore, binding sites for early/immediate gene products (i.e., E-Box and Egrl) may explain AcChoEase expression in tumor tissues and may relate to the tumorigenic amplification of this gene (27,28). The existence of an NF-KB element within the first intron could possibly imply that expression of the ACHE gene in lymphocytes is subject to regulation by transcription factors binding this intron and affecting cell cycle-related control, limited to the Go-G1 transition phase (16).…”
supporting
confidence: 66%
“…In embryonic life, definition of the role of cholinesterases in cellular proliferation and differentiation have started the investigations on possible involvement of BChE and AChE in tumorogenesis. Abnormal expression of both BChE and AChE, and in vivo amplification of their genes have been observed in intracranial neoplasms such as meningioma (67), glioma (68), and acuostic neurinomas (69), lung cancers (70), megakaryocytopoietic disorders and leukemias (71), ovarian tumors (72). It is also shown that AChE and BChE modulate cell adhesion in human neuroblastoma cells (62).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Since tightly folded G+C-rich DNA sequences display distinct replication patterns during the cell cycle (27), we wished to examine whether this sequence domain is faithfully replicated in vivo, particularly in cases where AcChoEase gene amplification occurs (5,7). For this purpose, DNA hybridization was performed using 5' and 3' regional probes: (i) an Sph I fragment including the putative attenuator sequence, derived from the 5' GNACHE clone, and (ii) the 3' NBG8A probe, similar to the 1.5-kb fragment that was previously used to detect the AcChoEase gene amplification phenomenon (5, 7).…”
Section: Resultsmentioning
confidence: 99%
“…LA); its restriction pattern should resemble that of the native AcChoEase gene. DNA was transferred to GeneScreen (DuPont/ NEN) and hybridized with the 32P-labeled 5' and 3' probes as detailed (5 similarly digested transferred plasmid DNA including the AcChoEase genomic DNA insert was employed as a control for the genomic blots ( Fig. 3B; refs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation